2017
DOI: 10.2152/jmi.64.39
|View full text |Cite
|
Sign up to set email alerts
|

High intensity zone in lumbar spine and its correlation with disc degeneration

Abstract: : Purpose ; To investigate the prevalence, clinical significance of high intensity zone (HIZ), and associated disc degeneration. Materials and methods ; We undertook retrospective analysis of 228 patients, aged from 15 to 55 years, who had undergone magnetic resonance (MR) imaging of lumbar spine in outpatient clinic from 2013 to 2014. HIZ was defined as a presence of high intensity signal in the annulus on T2-weighted images. All HIZ positive discs were classified according to Pfirrmann grading system for pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(12 reference statements)
1
7
0
Order By: Relevance
“…Lam et al 14) demonstrated a significant correlation between abnormal disc morphology and the presence of HIZ. Subash et al 15) reported that the presence of HIZ was directly correlated with increased incidence of lumbar disc degeneration and that the prevalence of degeneration was significantly higher in patients with HIZ in the lower three lumbar levels. Our result was consistent with that of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lam et al 14) demonstrated a significant correlation between abnormal disc morphology and the presence of HIZ. Subash et al 15) reported that the presence of HIZ was directly correlated with increased incidence of lumbar disc degeneration and that the prevalence of degeneration was significantly higher in patients with HIZ in the lower three lumbar levels. Our result was consistent with that of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…40) Such advances ultimately resulted in modern high-resolution images and has since allowed the characterization and identification of various degenerative spinal phenotypes, such as disc degeneration, disc displacement, disc space narrowing, structural and non-structural endplate abnormalities, highintensity zones, and osteophytes (Figures 3, 4, 5). 9,[41][42][43][44][45][46][47][48] These phenotypes have since been heavily associated with concomitant symptomatology and are thought to contribute to axial neck and/or back pain, worse surgical outcomes, and decreased health-related quality of life scores. 44,[49][50][51][52][53] Notably, MRI has allowed for particularly detailed characterization of intervertebral discs and endplates, leading to the development of validated classification schemes as proposed by Pfirrmann and Modic.…”
Section: Mrimentioning
confidence: 99%
“…8 In the past few decades, there has been considerable debate over the predictive value of HIZ on lumbar MR images for LBP. 4,[9][10][11][12][13][14] However, increasing evidence suggests that HIZ, the classical sign described by Aprill and Bogduk, 6 indicates a part of the natural history of disc degeneration, 14,15 but is not a reliable indicator of symptomatic IDD. 4,10,11,14 In practice, HIZ signs appear in various forms and can be characterized utilizing spatial location and analysis with lumbar MR imaging sequences.…”
Section: Introductionmentioning
confidence: 99%